Pelatihan Mendeley sebagai Alat Penyusun Referensi Penulisan Karya Ilmiah Guru SMP Negeri 1 Medan - Muhammad Dedi Irawan; Samsudin Samsudin; Muhammad Irwan Padli Nasution; Ilka Zufria; Suendri Suendri; Ali Ikhwan (Universitas Islam Negeri Sumatera Utara, 2020)
The reason for this examination was to decide the significance of Mendeley's reference to the board programming and to prepare instructors in arranging references in the planning of logical papers. This exploration is a result of network administration that has been done by teachers at the 1 Medan State Junior High School. This examination technique is subjective with a contextual investigation approach. This investigation requests that the educator record methods of masterminding logical papers in sorting out references utilizing reference the board programming, for example, Mendeley in entering references and gathering a list of sources. The subjects of this investigation were 16 instructors from SMP Negeri 1 Medan. The outcomes got from this examination are that instructors can look for references from sources, for example, Google Scholar, and add to Mendeley references, can improve definite data on the data that has been acquired, and can synchronize the Microsoft Word application. From this examination, it very well may be reasoned that Mendeley's reference the executives programming has the exactness of composing citations and arrangements of references which altogether helps educators recorded as a hard copy logical papers.